IMPLEMENTASI PROGRAM BIMBINGAN DAN KONSELING DI MTS NEGERI 3 PEKANBARU TAHUN 2017 - Shelshi Novisa; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The reality of the implementation of the program guidance and counseling in school still not run in accordance with the rules that have been set. There are still found schools that use BK pattern 17 plus. According to the Minister of Education and Culture Regulation No. 111 of 2014, the implementation of guidance and counseling in schools should use the Comprehensive Program, which is explained that the guidance and counseling program components include basic services, specialization services and individual planning, responsive services, and system support. The research objectives are: 1) to know the types and contents of guidance and counseling program, and 2) to know the implementation of guidance and counseling program in MTs Negeri 3 Pekanbaru in 2017. The method that researchers use is descriptive qualitative method. The results showed that BK program implementation in school using BK 17 plus and BK Comprehensive pattern. This is due to differences in the application of curriculum to students of class 7 and 8 who have been using the curriculum 2013. While the students of class IX still use the curriculum KTSP. So, BK program implementation using BK 17 Plus pattern has been running well, because it has scheduled implementation time. While the implementation of the BK program that uses Comprehensive has not run well, due to lack of service implementation guidelines, and no specific time to implement the program BK. Keywords: guidance and counseling programs, implementation.